Nothing Ventured, Nothing Gained: A Scoping Review and Future Research Directions for Public Sector Intrapreneurship - Geneviève Morin; Étienne Charbonneau (Public Administration Quarterly, 2026)
The acceleration of transformations in governance systems, organizational designs, and state-market relations in the 2020s has placed organizational intrapreneurship at the heart of adaptive capacities. Despite the rapid growth of research on intrapreneurship, public entrepreneurship, and organizational entrepreneurship, the literature remains fragmented across sectors, levels of analysis, and theoretical traditions. This scoping review synthesizes 61 empirical, conceptual or theoretical studies from 2020s and repositions intrapreneurship as a multilevel governance capacity embedded in evolving institutional dynamics. The synthesis articulates an integrated framework encompassing macro (institutions and governance architectures), meso (leadership and hybrid structures), and micro (professional identity and sensemaking) levels in the public sector. It also formulates a forward-looking agenda that aims to strengthen theoretical cumulativeness, methodological robustness, and the translatability of results into actionable policies and initiatives.